Microbiome Analysis Reveals the Presence of Bartonella spp. and Acinetobacter spp. in Deer Keds (Lipoptena cervi) - Regier, Yvonne; Komma, Kassandra; Weigel, Markus; Pulliainen, Arto T.; Göttig, Stephan; Hain, Torsten; Kempf, Volkhard A. J. (Frontiers in Microbiology, 2018)
The deer ked (Lipoptena cervi) is distributed in Europe, North America and Siberia and mainly infests cervids as roe deer, fallow deer and moose. From a one health perspective, deer keds occasionally bite other animals or humans and are a potential vectors for Bartonella schoenbuchensis. This bacterium belongs to a lineage of ruminant-associated Bartonella spp. and is suspected to cause dermatitis and febrile diseases in humans. In this study, we analyzed the microbiome from 130 deer keds collected from roe deer, fallow deer and humans in the federal states of Hesse, Baden-Wuerttemberg and Brandenburg, Germany. Endosymbiontic Arsenophonus spp. and Bartonella spp. represented the biggest portion (~90%) of the microbiome. Most Bartonella spp. (n=93) were confirmed to represent B. schoenbuchensis. Furthermore, Acinetobacter spp. were present in four samples, one of those was confirmed to represent A. baumannii. These data suggest that deer keds harbor only a very narrow spectrum of bacteria which are potentially pathogenic for animals of humans.